2010
DOI: 10.1186/1750-9378-5-20
|View full text |Cite
|
Sign up to set email alerts
|

Human papillomavirus-16 presence and physical status in lung carcinomas from Asia

Abstract: BackgroundAlthough human papillomavirus (HPV) genome has been detected in lung cancer, its prevalence is highly variable around the world. Higher frequencies have been reported in far-east Asian countries, when compared with European countries. The present study analysed the HPV-16 presence in 60 lung carcinomas from the Asian countries China, Pakistan and Papua New Guinea.ResultsHPV-16 was present in 8/59 (13%) samples. According to histological type, HPV-16 was detected in 8/18 (44%) squamous cell carcinomas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
16
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(18 citation statements)
references
References 26 publications
(27 reference statements)
2
16
0
Order By: Relevance
“…10,11,26,27 In the present study too, we observed a significant association of SCC with HPV (P 5 0.01). 10,11,26,27 In the present study too, we observed a significant association of SCC with HPV (P 5 0.01).…”
Section: Discussionsupporting
confidence: 67%
See 1 more Smart Citation
“…10,11,26,27 In the present study too, we observed a significant association of SCC with HPV (P 5 0.01). 10,11,26,27 In the present study too, we observed a significant association of SCC with HPV (P 5 0.01).…”
Section: Discussionsupporting
confidence: 67%
“…Although HPV has been found to be associated with all histological subtypes of lung cancer; the association is strongest with SCC. 10,11,26,27 In the present study too, we observed a significant association of SCC with HPV (P 5 0.01).…”
Section: Discussionsupporting
confidence: 67%
“…For instance, human papillomavirus (HPV) infection has been observed in association with cases of lung cancer in many studies worldwide, suggesting a role for HPV as an aetiological agent of lung cancer (Aguayo et al , 2007; Klein et al , 2009; Rezazadeh et al , 2009; Prabhu et al , 2012). However, the results are discrepant among research groups (Brouchet et al , 2005) and underline some geographical variations (Miyagi et al , 2000; Aguayo et al , 2010; Goto et al , 2011). …”
mentioning
confidence: 83%
“…Aguayo et al . observed statistically significant differences in HPV 16 prevalence between histological cancer types: they detected HPV16 in 44% SCCs, whereas ACs and SmCCs were HPV16 negative . A Chinese study found that HPV infection is more prevalent in SCC (59.8%) than in AC (17.5%) .…”
Section: Discussionmentioning
confidence: 98%